2018
DOI: 10.1002/aenm.201800138
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Inorganic Binary Alkaline Halide to Passivate Defects in Low‐Temperature‐Processed Planar‐Structure Hybrid Perovskite Solar Cells

Abstract: Planar perovskite solar cells obtained by low‐temperature solution processing are of great promise, given a high compatibility with flexible substrates and perovskite‐based tandem devices, whilst benefitting from relatively simple manufacturing methods. However, ionic defects at surfaces usually cause detrimental carrier recombination, which links to one of dominant losses in device performance, slow transient responses, and notorious hysteresis. Here, it is shown that several different types of ionic defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
178
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(183 citation statements)
references
References 53 publications
5
178
0
Order By: Relevance
“…An average PCE of 0.99% from 68 cells is achieved (Figure S7b, Supporting Information). The J – V curves of our devices show a hysteresis under forward and backward scanning direction (Figure S7a, Supporting Information) that can be attributed to the non‐optimized charge extraction interfaces as demonstrated by recent reports . The corresponding maximum power point output performance is shown in Figure b.…”
supporting
confidence: 68%
“…An average PCE of 0.99% from 68 cells is achieved (Figure S7b, Supporting Information). The J – V curves of our devices show a hysteresis under forward and backward scanning direction (Figure S7a, Supporting Information) that can be attributed to the non‐optimized charge extraction interfaces as demonstrated by recent reports . The corresponding maximum power point output performance is shown in Figure b.…”
supporting
confidence: 68%
“…Recently, high performing perovskite devices have increased compositional complexity by incorporating Group 1 (alkali metals) elements such as Na, K, or Cs. These materials have also been adopted as a dopant or an additional layer on ETLs for alleviating trap states at the ETL/perovskite interface . Seo et al reported a modification of the TiO 2 surface by CsBr to strengthen its interaction with the perovskite for rapid extraction of photogenerated electrons which lead to very high fill factor close to 80% from their cells.…”
Section: Passivation Of Carrier Transport Layer (Ctl)mentioning
confidence: 99%
“…Such cell has V oc of 1.14 V and PCE up to 21% with negligible hysteresis. Liu et al deposited KCl layer on the c‐TiO 2 layer and confirmed that TiO 2 /perovskite interfacial recombination was suppressed, resulting in an increase of V oc (1.13 V) and the elimination of hysteresis.…”
Section: Passivation Of Carrier Transport Layer (Ctl)mentioning
confidence: 99%
“…Figure 5a indicates that the PL was quenchedb ecause of fast electron transfer to ETLs, indicatingt hat more electron holes were transported from the perovskite layer to the perovskite/ETL interface. [24,32] The ammonium cation, the radiuso fw hich is close to Rb, [15] tends to combine with perovskite film and passivate positive ion vacancies. Previous studies have shown that Cl À in the interface has no significant contribution to the blueshift of the perovskite peak, confirming that NH 4 + effectively passivates trap-states of the perovskite absorber film.…”
Section: Resultsmentioning
confidence: 99%